Septal deviation in the nose of the longest faced crocodylian: A description of nasal anatomy and airflow in the Indian gharial (Gavialis gangeticus) with comments on acoustics. Issue 10 (23rd November 2021) - Bourke, Jason M.; Fontenot, Nicole; Holliday, Casey
Abstract: The remarkably thin rostrum in the Indian gharial ( Gavialis gangeticus ) imparts challenges to nasal physiology. Competition for space in the slim jaws necessitates a thin nasal septum, leaving this taxon susceptible to nasal passage abnormalities such as septal deviation. Here we describe the nasal anatomy of gharials based on multiple individuals including one that showcases an extreme instance of nasal septum deviation. We found that gharials have both confluent nostrils and choanae, which may be important for their unique nasal acoustics. The deviated nasal septum in the female showed distinct waviness that affected the nasal passages by alternately compressing them. We performed a computational fluid dynamic analysis on the nasal passages to visualize the effects of septal deviation on airflow. Our analysis found the deviated septum increased nasal resistance and wall shear stress during respiration, resulting in unequal distribution of the air field between both sides of the nasal passage. Our findings indicate that gharials—and potentially other longirostrine crocodylians—may be particularly susceptible to septal deviations. Lastly, we observed pterygoid bullae to be present in both sexes, though their morphology differed. Airflow in the male pterygoid bullae produced a Bernoulli effect which may be responsible for the unique "pop" sounds recorded in this species.